Clinical Assessment of the Violent Adolescent - Cornell, Dewey G. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
School psychologists may be asked to assess potentially violent adolescents. Research on predicting violence has demonstrated that: (1) most studies show poor predictive ability; (2) clinicians tend to overpredict violence; (3) prediction is difficult because the base rate is low; and (4) the best single predictor is past violent behavior. New perspectives on predicting violence suggest that aggressiveness is surprisingly stable over time, that long-term risk is not the same as imminent danger, that situational factors must be assessed, and that there may be multiple developmental pathways to violence. A study of 72 adolescents who had committed homicide revealed important differences in the backgrounds of nonpsychotic, violent adolescents. One group, who committed violent acts in the course of other criminal activity, had a history of juvenile delinquency, school problems, and substance abuse. Another group, who committed violent acts in reaction to interpersonal conflict, were relatively well-adjusted in comparison to the crime group. They tended to have school and community adjustment problems, although they appeared to be experiencing more environmental stress at the time of their violent behavior. In assessing potentially violent adolescents, counselors should review the purpose for the assessment with the adolescent, focus on recent violent behavior, assess situational factors, plan a course of action and discuss it with the adolescent, and follow through with appropriate action after the evaluation. (NB)
ERIC Note: Paper presented at the Annual Meeting of the National Association of School Psychologists (19th, New Orleans, LA, March 4-8, 1987). For related document, see CG 020 420.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adjustment (to Environment); Adolescents; Delinquency; Elementary Secondary Education; Evaluation Methods; Personality Traits; Predictor Variables; School Counselors; Violence; Information Analyses; Speeches/Meeting Papers